2014
DOI: 10.1002/pon.3735
|View full text |Cite
|
Sign up to set email alerts
|

The information and decision support needs of older women (>75 yrs) facing treatment choices for breast cancer: a qualitative study

Abstract: M (2014). The information and decision support needs of older women (>75 yrs) facing treatment choices for breast cancer : a qualitative study. 24 (8),[878][879][880][881][882][883][884]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 38 publications
2
69
0
5
Order By: Relevance
“…An important aspect in this decision process is the opinion of the patient. Burton et al studied the information needs of older women with breast cancer [ 38 •]. All patients wanted information on the impact of the treatment on independence, practicalities of treatment and healthcare professional’s recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect in this decision process is the opinion of the patient. Burton et al studied the information needs of older women with breast cancer [ 38 •]. All patients wanted information on the impact of the treatment on independence, practicalities of treatment and healthcare professional’s recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…All patients wanted information on the impact of the treatment on independence, practicalities of treatment and healthcare professional’s recommendations. When patients were asked what treatment they preferred, there were two frequent answers: optimal disease control by surgery or minimal disruption of life by primary endocrine therapy [ 38 •]. Another study investigated surgeon’s opinions and concluded that 93% of surgeons believed that primary endocrine therapy should be limited to elderly women who are not fit for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These suggestions require thoughtful implementation in order to be realized most optimally, since 1) the clinic environment can be quite busy and individual visits with oncology care providers are shorter than ideal; 2) a one-size-fits-all strategy will not be appropriate for risk communication or for side effect management; and 3) messaging must be continual and consistent to help support ET adherence and persistence for 5–10 years, as recommended. Strategies to address these challenges may include using more lay or peer navigators in the clinic (who can afford to spend more time with each individual patient), 18 , 19 tailoring risk communication 20 and side effects management to better fit with the individual patient’s experience, 21 , 22 and consolidating evidence-based information about effective management of ET-related side effects, including pharmacological and nonpharmacological options. 22 …”
Section: Discussionmentioning
confidence: 99%
“…An acknowledgement of having already lived a long life allowed some older women to pragmatically accept their diagnosis [25]. Four studies described how some women expressed shock, anxiety, and self-blame with the diagnosis [21,25,28,31]. Husain et al described how these women particularly feared dying, being left disfigured, not knowing what to do, and leaving others behind [25].…”
Section: Patient Experience During the Breast Cancer Diagnosis Phasementioning
confidence: 99%
“…Older women preferred information from their physicians, with specialist nurses also identified as trusted and useful [21,23]. Four studies reported how older women preferred written information over electronic [21,23,24,32].…”
Section: Patient Experience During the Decision-making Phasementioning
confidence: 99%